AUDITORIA DE MARKETING NA EMPRESA MARINO FOGÕES - François, Luiza Da Costa; Zanon, Carine Hermany; Hampel, Gustavo Da Silva; Ledermann, Martin; Rotili, Liane Beatriz (Salão do Conhecimento, 2018)
Projeto de pesquisa realizado no curso de Administração da Unijuí